Application of comprehensive nursing combined with ISBAR handover approach in the nursing of patients with placental abruption - Yang, Qing; Liu, Ningning; Xie, Wanyang (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
Objective  The research for this paper was conducted to unveil the effect of comprehensive nursing combined with the Identification-Situation-Background-Assessment-Recommendation (ISBAR) handover approach in the nursing of patients with placental abruption.Methods  The 40 cases of placental abruption patients admitted to the Women’s Hospital School of Medicine Zhejiang University from May 2021 to May 2022 were subjected to conventional basic nursing combined with traditional handover tool intervention, which was recorded as the control group; the 40 cases of placental abruption patients admitted to the Women’s Hospital School of Medicine Zhejiang University from June 2022 to June 2023 were subjected to comprehensive nursing combined with ISBAR handover tool intervention, which was recorded as the observation group. Maternal and infant outcomes, the quality of nurse handover, and the psychological burden [State Anxiety Inventory (S-AI), Trait Anxiety Inventory (T-AI), Distress Thermometer (DT), and General Self-Efficacy Scale (GSES)] were observed in the two groups, and the satisfaction with nursing was also assessed by using a self-administered satisfaction scale in the two groups.Results  The rate of normal delivery of patients in the observation group was higher and the rate of cesarean section and the total incidence of complications were lower than that of the control group. The 1- and 5-min Apgar scores of the newborns in the observation group were higher and the total complication rate was lower than that in the control group. Nurses in the observation group had higher scores for nursesʼ shift handover quality. S-AI, T-AI, and DT scores were lower in both groups after the intervention and were lowest in the observation group; GSES scores were higher and were highest in the observation group. Satisfaction with nursing was higher in the observation group than in the control group.Conclusion  Comprehensive nursing combined with the ISBAR handover approach applied to the clinical care of patients with placenta abruption can effectively improve the outcomes of mothers and infants, enhance the quality of nursesʼ shift handovers, reduce the psychological burden of patients and increase nursing satisfaction.
Keywords: Placental abruption; Comprehensive nursing; ISBAR handover approach